FOUNDATIONS OF SELECTION OF INNOVATION STRATEGY FOR INDUSTRIAL COMPANIES IN RUSSIAN FEDERATION - U. Blinova; E. Shcherbinina (Вестник университета, 2016)
The arguments proving the necessity of innovation way of development for Russian industrial companies are presented. Three main directions of forming strategies formation alongside circumstances affecting them are outlined. The main advantages and disadvantages of the suggested strategies are considered.